2014
DOI: 10.1021/jp501707n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca2+ on the Steady-State and Time-Resolved Emission Properties of the Genetically Encoded Fluorescent Sensor CatchER

Abstract: We previously designed a calcium sensor CatchER (a GFP-based Calcium sensor for detecting high concentrations in the high calcium concentration environment such as ER) with a capability for monitoring calcium ion responses in various types of cells. Calcium binding to CatchER induces the ratiometric changes in the absorption spectra, as well as an increase in fluorescence emission at 510 nm upon excitation at both 395 and 488 nm. Here, we have applied the combination of the steady-state and time-resolved optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…For the indirectly excited (at 372 nm) R∗O − form, a fast quenching component within the first 2 ns was detected, which was followed by a long asymptotic decay closely approaching the lifetime of the directly excited R∗O − . Further lifetime studies in D 2 O confirmed that such a lifetime increase of G-CatchER + is a result of delayed proton geminate recombination and is caused by a combination of acid-base equilibrium and arrangement differences of the proton network with the chromophore between Ca 2+ free and the Ca 2+ binding form ( Zhuo et al., 2015 ). Ca 2+ also exhibited a strong inhibition of the excited state proton transfer nonadiabatic geminate recombination in protic (versus deuteric) medium ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 89%
“…For the indirectly excited (at 372 nm) R∗O − form, a fast quenching component within the first 2 ns was detected, which was followed by a long asymptotic decay closely approaching the lifetime of the directly excited R∗O − . Further lifetime studies in D 2 O confirmed that such a lifetime increase of G-CatchER + is a result of delayed proton geminate recombination and is caused by a combination of acid-base equilibrium and arrangement differences of the proton network with the chromophore between Ca 2+ free and the Ca 2+ binding form ( Zhuo et al., 2015 ). Ca 2+ also exhibited a strong inhibition of the excited state proton transfer nonadiabatic geminate recombination in protic (versus deuteric) medium ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 89%
“…Several other nonratiometric single-FP sensors also show a substantial change in fluorescence lifetime, including the cytosolic and endoplasmic reticulum calcium sensors, RCaMP (28) and CatchER (31). Direct mutation of the betabarrel of the GFP to make it more conformationally sensitive has also successfully produced a single-FP sensor for PKA with a usable lifetime change (6).…”
Section: Discussionmentioning
confidence: 99%
“…The first ER-targeted genetically-encoded Ca 2+ indicator (GECI) was an aequorin construct specifically targeted to the ER lumen that, however, has been used exclusively for measurements in cell populations [ 10 ]. As to GECIs suitable for single cell analysis, in the last decade different single fluorescent protein (FP) Ca 2+ sensors targeted to the ER have been generated: R-CEPIA1er and G-CEPIA1er [ 11 ], ER-LAR-GECO1 [ 12 ], CatchER [ 13 ], GCaMPer [ 14 ]. These non-ratiometric probes are, in general, very difficult to calibrate in live cells and their use is primarily qualitative.…”
Section: Introductionmentioning
confidence: 99%